SKILLS OF TEACHER IN TEACHING HISTORY OF ISLAMIC CULTURE: THE CASE STUDY IN MTS MA’ARIF KEJAJAR WONOSOBO - Ubayin Ubayin; Karwadi Karwadi (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2018)
This study is used a qualitative approach and intended to describe the teacher's skills in teaching History of Islamic culture at MTs Maarif Kejajar Wonosobo, and to analyze its suitability for the implementation of learning according to the Curriculum 2013. Data are collected by passive participatory observation. The results of the observations were analyzed by data reduction, data display, and conclusion drawing. The results showed that the teacher's skills in reinforcement, variation stimulus, set induction and closure, classroom management and questioning, and mastering substances are good. However, the teacher has not developed many learning models following Curriculum 2013. The teacher conducts learning activities in the form of preliminary, main and closing activities with good performance, but it is relatively not useful in applying learning methods, because the teacher does not apply student-centered learning method as recommended or instructed in Curriculum 2013.